2018
DOI: 10.3390/en11102642
|View full text |Cite
|
Sign up to set email alerts
|

Frosting Phenomenon and Frost-Free Technology of Outdoor Air Heat Exchanger for an Air-Source Heat Pump System in China: An Analysis and Review

Abstract: Frost layer on the outdoor air heat exchanger surface in an air-source heat pump (ASHP) can decrease the system coefficient of performance (COP). Although the common defrosting and anti-frosting methods can improve the COP, the periodic defrosting not only reduces the system energy efficiency but also deteriorates the indoor environment. To solve these problems, it is necessary to clearly understand the frosting phenomenon and to achieve the system frost-free operation. This paper focused firstly on the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 87 publications
1
5
0
1
Order By: Relevance
“…The results of the experiment confirmed that, on average, in this zone, ASHP reference defrosting interval is 45-90 min. Moreover, the results were consistent with the results of the previous studies when the evaporator was freezing impaired heat transfer processes [5] and reduced energy efficiency [6]. The three test/representative periods showed that the ASHP COP decreases as the ambient temperature decreases and the humidity increases, and vice versa: as the ambient temperature rises and the humidity decreases.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the experiment confirmed that, on average, in this zone, ASHP reference defrosting interval is 45-90 min. Moreover, the results were consistent with the results of the previous studies when the evaporator was freezing impaired heat transfer processes [5] and reduced energy efficiency [6]. The three test/representative periods showed that the ASHP COP decreases as the ambient temperature decreases and the humidity increases, and vice versa: as the ambient temperature rises and the humidity decreases.…”
Section: Resultssupporting
confidence: 90%
“…As the outdoor temperature drops, the COP decreases, and at high relative humidity, there is a risk of the evaporator freezing, which increases the system's energy consumption, energy costs and impairs the heat transfer [5]. There are various defrosting and anti-frosting methods that can be used; however, defrosting also reduces the energy efficiency of the system and can negatively affect the micro-climate indoors [6]. Possible improvements of ASHP units in terms of frost retarding and defrosting are reviewed by Mengjie et al [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to improve the heating performance of ASHPs and improve indoor thermal comfort, research on effective defrosting and frost suppression technology is vital. 17,18…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to improve the heating performance of ASHPs and improve indoor thermal comfort, research on effective defrosting and frost suppression technology is vital. 17,18 Defrosting methods are available, including reverse cycle defrosting (RCD), 4,[19][20][21] hot gas bypass defrosting, 22,23 electric heating defrosting, [24][25][26] compressor shutdown defrosting, 27,28 and ultrasonic vibration defrosting. 29 Currently, RCD is the mainstream defrosting method; it can achieve rapid defrosting and significantly improve the heating capacity and coefficient of performance (COP) of ASHPs.…”
Section: Introductionmentioning
confidence: 99%
“…Although each of the above mentioned potential real-life applications of super-nonwetting coatings has its significance and importance, the possibility for passively preventing (with no external energy applied) the ice and snow accumulation in harsh environments stands out as an approach with extremely high economic and societal impact [39][40][41][42][43][44]. The reason for such a statement is simple and associated with the detrimental effect of icing on many industrial and social sectors including aviation [42], renewable energy production [44], power and chemical plants [45,46], road infrastructure [41,43], overhead lines [47], solar panels, off-shore oil platforms [44] and many more. Virtually, the icing is undesirable literally everywhere in our daily routine, except may be in the restaurant industry, where the ice cubes are used to cool the beverages.…”
Section: Introductionmentioning
confidence: 99%